AVIATION TRAINING OF SOCIAL WORK PROFESSIONALS THROUGH DISTANCE EDUCATION DURING WAR TIME - Sanzharovets, Valentina (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The peculiarities of the training process of social work specialists for the aviation industry during distance learning during wartime are revealed. The content of the indicated direction stimulates applicants to be constantly in the work process, therefore there is a need for new knowledge, ways of mastering the material of the programs offered by specialists. Various forms and methods are used in the system of scientific and methodological support of the process of developing the innovative potential of teachers of higher education institutions.